2019
DOI: 10.1038/s41533-019-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects and acceptability of implementing improved cookstoves and heaters to reduce household air pollution: a FRESH AIR study

Abstract: The objective was to evaluate the effectiveness and acceptability of locally tailored implementation of improved cookstoves/heaters in low- and middle-income countries. This interventional implementation study among 649 adults and children living in rural communities in Uganda, Vietnam and Kyrgyzstan, was performed after situational analyses and awareness programmes. Outcomes included household air pollution (PM 2.5 and CO), self-reported respiratory symptoms (with CCQ and MRC-breathless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
(43 reference statements)
1
29
1
Order By: Relevance
“…On the longer-term behavioural level, acceptability of the improved stoves was high: 100% of the stove users in Kyrgyzstan and 89.8% in Vietnam recommended the new stove to others. Stove stacking occurred in 15% of the Kyrgyz households and 85.5% of the Vietnamese 39 . In Vietnam, the improved cookstoves were often considered too small: 44% continued to use the traditional cookstove for cooking every day and 36% for several times a week.…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…On the longer-term behavioural level, acceptability of the improved stoves was high: 100% of the stove users in Kyrgyzstan and 89.8% in Vietnam recommended the new stove to others. Stove stacking occurred in 15% of the Kyrgyz households and 85.5% of the Vietnamese 39 . In Vietnam, the improved cookstoves were often considered too small: 44% continued to use the traditional cookstove for cooking every day and 36% for several times a week.…”
Section: Effectivenessmentioning
confidence: 99%
“…However, stove stacking occurred substantially more frequently in Vietnam in our study, suggesting that, besides knowledge, other causes also contribute to inadequate clean cooking practices. For example, characteristics of the stove are known to influence implementation success 15,16 ; Vietnamese participants in the FRESH AIR stove programme considered their stove too small and continued to use their old one concurrently 39 . Hence, with many factors contributing to the adequate use of improved stoves, programme implementation should ideally go hand in hand with all favourable factors, such as favourable market developments and policies 15,16 .…”
Section: Contextmentioning
confidence: 99%
“…We most welcome the comment by Thakur, van Schayck and Boudewijns 1 on our article on the effects and acceptability of implementing improved cookstoves. 2 Adoption rates of improved cookstoves by local communities are often strikingly low. The authors underline the urge to advance cookstove implementation strategies, and reinforce the approach used in the FRESH AIR project.…”
mentioning
confidence: 99%
“…The authors underline the urge to advance cookstove implementation strategies, and reinforce the approach used in the FRESH AIR project. 2 They highlight several important factors to increase adoption success and call for further research on the topic. We want to build on this comment by reflecting on decades of substantial discrepancies between the disappointing adoption rates of improved cookstoves, and the subsequent failure to adapt implementation strategies accordingly.…”
mentioning
confidence: 99%
“…This was done in another FRESH AIR study by conducting an initial explorative mixed-method rapid assessment of the local context [96]. The results of this assessment informed implementation strategies for improved cookstove interventions in Uganda, Vietnam and Kyrgyzstan [97]. First, the context assessment revealed that communities and their health workers poorly understood the risk of household air pollution and therefore felt no need for change.…”
Section: Ensure Compatibilitymentioning
confidence: 99%